Offences and defences : - Gardner, John (Oxford University Press, 2007)
This collection, of eleven of John Gardner's papers in philosophy of criminal law from the last fifteen years, makes clear how distinctive and incisive his contributions have been to our understanding of the structure and proper aims of criminal law, of how criminal offences should be analysed and defined, and of the character and significance of responsibility. It also shows how much criminal law theory depends on, and is enriched by, a serious engagement with deeper issues in moral and political philosophy (which is one reason why the collection should interest moral and political philosophers even if they are not directly interested in criminal law). The collection is made yet more valuable by the addition of a substantial 'Reply to Critics'